Pengaruh Penggunaan Gadget Terhadap Kedisiplinan Shalat Remaja Desa Tanjungsari Petanahan Kebumen - Mutoharoh, Siti; Kurniawan, Benny (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The background for conducting this research is because there are problems related to the use of gadgets by teenagers which can make them forget prayer times when using gadgets. Given the background to this problem, the aim of this research is to find out whether there is an influence from the use of gadgets on the prayer discipline of teenagers in Tanjungsari Village, Petanahan, Kebumen. This research includes field research with a quantitative type of research. The data was obtained from the results of data collection techniques using questionnaires and interviews. The sample used for research was 30 teenagers from Dukuh Gandu, Tanjungsari Village, Petanahan, Kebumen. The data analysis uses a simple linear regression analysis technique to determine whether or not there is an influence from the independent variable Use of Gadgets and the dependent variable Prayer Discipline. After conducting research, the results showed that the calculated F value was 12,473 with a significance level of 0.001 < 0.05, which means the significance value is smaller than 0.05, so it can be concluded that there is an influence of gadget use on prayer discipline. Therefore, the research hypothesis Ha is accepted and Ho is rejected, which means that there is an influence of the use of gadgets on the prayer discipline of teenagers in Tanjungsari Village, Petanahan, Kebumen. The influence of using gadgets on prayer discipline is 30.8%.